Pola dan Strategi Dakwah Dalam Moderasi Beragama - Sapri Yani Hasibuan; Erwan Efendi; Deni Armanda; Yusuf Saifulloh (Da'watuna: Journal of Communication and Islamic Broadcasting, 2023)
Religion moderation has multiple characteristics, Indonesian society is multicultural. Culture, religion, race, language, ethnicity, tradition, and others are examples of diversity. Even though it is not a religious country, its people are closely related to religion. Life, and the constitution guarantees freedom of religion. The first precept of Pancasila, "Belief in One Almighty God", indicates that this state system is based on Indonesian religious principles, teachings, and values. Every citizen faces the challenge of striking a balance between national commitments and religious rights. The purpose of this paper is to help readers understand the methods and strategies of da'wah, in Indonesia itself there are still many obstacles to religious moderation. In the evolution of Islamic society, the study of da'wah is inseparable from the strategies outlined. The goals and desires of this da'wah may not necessarily be fulfilled in accordance with expectations if we do not conceptualize them. Meanwhile strictly speaking, in each meeting they presented several examples in their respective religions. Despite the fact that they are interested in maintaining religious harmony. In addition, it includes the possibility of preaching to all religions. Whereas everyone must believe in and maintain a good relationship with their God and with each other as well. An advanced Indonesian nation can benefit from a tolerant, peaceful and harmonious religious and national life through religious moderation. Keywords: Pattern, Strategy, Da'wah, and Moderation of Religion.